2000
DOI: 10.1128/jvi.74.19.9083-9089.2000
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD8 T Cells by Vaccination with Recombinant Adenovirus Expressing Human Papillomavirus Type 16 E5 Gene Reduces Tumor Growth

Abstract: The potential of the E5 protein as a tumor vaccine candidate has not been explored yet. In this study, we evaluate the human papillomavirus type 16 (HPV-16) E5 protein delivered by an adenovirus vector as a tumor vaccine for cervical lesions. The results demonstrate that a single intramuscular injection of a recombinant adenovirus carrying the HPV-16 E5 gene into syngeneic animals can reduce the growth of tumors which contain E5 gene expression. Moreover, the E5 vaccine-induced tumor protection occurs through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 61 publications
1
46
1
4
Order By: Relevance
“…In E5-transformed cells, the E5 protein binds directly to the vacuolar ATPase and inhibits its activity. This impairs endosome acidi®cation and EGF receptor degradation, resulting in increased recycling of the receptor to the cell surface and enhanced receptor signaling HPV16 E5 can elicit cytotoxic T lymphocytes that can inhibit the growth of murine tumor cells engineered to express the viral protein (Liu et al, 2000). Further study of the papillomavirus E5 proteins will continue to shed light on viral transformation and replication, cellular signal transduction and organelle function, carcinogenesis, and the assembly of transmembrane protein complexes.…”
Section: Resultsmentioning
confidence: 99%
“…In E5-transformed cells, the E5 protein binds directly to the vacuolar ATPase and inhibits its activity. This impairs endosome acidi®cation and EGF receptor degradation, resulting in increased recycling of the receptor to the cell surface and enhanced receptor signaling HPV16 E5 can elicit cytotoxic T lymphocytes that can inhibit the growth of murine tumor cells engineered to express the viral protein (Liu et al, 2000). Further study of the papillomavirus E5 proteins will continue to shed light on viral transformation and replication, cellular signal transduction and organelle function, carcinogenesis, and the assembly of transmembrane protein complexes.…”
Section: Resultsmentioning
confidence: 99%
“…HPV E5 proteins may represent a target for therapeutic intervention. Recently, it has been shown that vaccination of mice with HPV-16 E5 can elicit cytotoxic T lymphocytes, which inhibit the growth of murine tumour cells (Liu et al, 2000;Chen et al, 2004). Successful E5 vaccination of affected cattle would provide an ideal model for the development of therapeutic vaccines for comparable human pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that mouse vaccination with HPV-16 E5 reduced the growth of tumours induced by E5-expressing cells (Liu et al, 2000). The potential for E5 vaccination should be validated in naturally occurring animal models and, moreover, the development of therapeutic/preventive immunoprophylaxis for these mucosal tumours would represent a model for human pathologies and could add precious indications for their treatment.…”
mentioning
confidence: 99%